The Professional Portfolio and the Attitude of the Pedagogical Specialists for Its Development - Tiha Delcheva (Педагогически форум)
A modern innovative technology that stimulates pedagogical specialists to build their own professional and personal image is the portfolio. The attitude to activity - mental state of readiness for activity, the result of the implementation of various dispositions to a particular form of response in pedagogical situations. A link between the substructures of the activity - motivational, target and operational. Its features are: integrity and unity; focus, stability and variability; individual character. The main functions are: stimulating, regulating variable, selective, reflective, corrective, transforming, etc. Through it, educators are reflexively aware of the psychological aspects of their work and stimulate their activity in developing a professional portfolio.